Network Marketing According to Sharia (Salam International Academic Journal, 2020)
Marketing is a requirement for the extension of any business, however, ‎in Islam this requirement must be rendered under Shari’ah Law. ‎Therefore, according to Islamic scholars, some forms of marketing are ‎unlawful and illegal, and some are absolutely accurate and permissible; ‎contemporary scholars have different views on the popular forms in ‎which it is necessary to purchase a product in order to obtain the right ‎to market it, some say that it falls under the permissible cycle of Islam ‎Law, however, some other disagree and say that it falls out of the ‎permissible cycle of Islamic Law, but it is better to be carried out under ‎some conditions and restrictions, and if some conditions and ‎restrictions are not considered, then it is unlawful and not permissible. ‎This is the proposition that is researched, and the result is presented to ‎the readers.‎